Quality Assessment Of Restored Satellite Data Based On Signal To Noise Ratio - Ahmad, Asmala; Shaun, Quegan (HIKARI Ltd, 2016)
A practical concept of assessing the quality of restored data based on signal to noise ratio (SNR) is reported. The data come from remote sensing satellite and has undergone restoration process due to atmospheric haze effects. The restoration involves removing haze mean due to haze scattering and haze randomness due to haze spatial variability. The results shows that the SNR of restored data can be computed if the haze mean and haze randomness components are known.